False Beliefs about Mathematics in Spanish Pre-Service Teachers and Relations with Math Anxiety - M. José Justicia-Galiano; Santiago Pelegrina (MDPI AG, 2024)
Teachers may hold beliefs about how students learn mathematics and about the subject itself. However, some of these beliefs, often referred to as "math myths", may be oversimplified ideas that appear valid but lack solid scientific evidence. This study was aimed to investigate the prevalence of math myths among Spanish pre-service teachers and compare it with the degree of support for these myths reported in previous studies; investigate the possible underlying structure of a set of false beliefs about math; and determine the relationships of certain math misconceptions with math anxiety. A total of 212 Spanish pre-service teachers were administered questionnaires about math myths and about general and math anxiety. The results showed prevalence patterns of each math misconception similar to those in previous studies. False beliefs about math showed weak or negligible correlations with each other and did not exhibit a discernible underlying structure. Furthermore, math anxiety was related to the belief that some individuals are perceived to possess a "math mind" while others do not. Our results suggest diverse origins for the development of different math myths, rather than the myths being the consequence of a single underlying factor. Finally, the endorsement of certain beliefs about who can do mathematics may contribute to negative emotions towards mathematics.